2011
DOI: 10.1016/j.coldregions.2011.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Frictional behavior of granular gravel–ice mixtures in vertically rotating drum experiments and implications for rock–ice avalanches

Abstract: Rapid mass movements involving large proportions of ice and snow can travel significantly further downslope than pure rock avalanches and may transform into debris-flows as the ice melts and as water from the stream network or water-saturated debris is incorporated. Currently, ice is thought to have three distinctive effects: 1) reduction of the friction within the moving mass itself, 2) increase of pore pressure as the ice melts and consequent reduction of the shear resistance of the flowing material, and 3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 56 publications
3
52
0
Order By: Relevance
“…The rotating drum experiments revealed bulk friction values between 0.50 and 0.72 for varying volumetric ice contents while real events having an estimated ice content of 10–100% reach much lower apparent coefficients of friction between 0.11 and 0.52 (Figure ). The friction coefficient in the laboratory experiments linearly decreases with increasing ice content, leading to a ~20% reduction of the friction for dry granular pure ice compared with gravel only (Schneider et al , ). The field data again does not obviously reveal such a trend except for the events with multi‐phase flow behavior (squares) where a slight trend for lower apparent coefficients of friction with higher ice contents could be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The rotating drum experiments revealed bulk friction values between 0.50 and 0.72 for varying volumetric ice contents while real events having an estimated ice content of 10–100% reach much lower apparent coefficients of friction between 0.11 and 0.52 (Figure ). The friction coefficient in the laboratory experiments linearly decreases with increasing ice content, leading to a ~20% reduction of the friction for dry granular pure ice compared with gravel only (Schneider et al , ). The field data again does not obviously reveal such a trend except for the events with multi‐phase flow behavior (squares) where a slight trend for lower apparent coefficients of friction with higher ice contents could be demonstrated.…”
Section: Resultsmentioning
confidence: 99%
“…(), and the experiments with the gravel–ice mixtures by Schneider et al . (). Herein we used measurements of the dynamic bulk friction coefficients of cold ( T ≈ −5 °C) and dry granular gravel–ice mixtures with varying volumetric ice contents (0.0856 m 3 material in the smaller drum and 0.4 m 3 in the larger drum).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Changes in the material characteristics of rock avalanches and fluidization during emplacement can lead to increased mobility (Deline, ; Hungr & Evans, ). Laboratory experiments (Schneider et al, ) and numerical modeling (Sosio et al, ) have demonstrated a reduction in friction of rock avalanche material upon the incorporation of ice. However, a lack of data and the difficulty of quantifying the amount of snow and ice in rock avalanche deposits contribute to a poor understanding of the degree to which ice entrainment affects the travel distance and overall emplacement characteristics of rock avalanches.…”
Section: Discussion: a Critical Evaluation Of Model Assumptions Uncementioning
confidence: 99%
“…While monosized or narrow size distributions can be described adequately by a single particle diameter, D p , for wide‐grain‐size distributions there is no agreement on the best effective diameter [ Stock and Dietrich , ]. Several studies have proposed that for a wide‐grain‐size distribution, a higher percentile than the median, such as the 84th percentile of the grain‐size distribution ( D 84 , 1 standard deviation above the mean grain size) may be a better effective grain size for quantifying inertial stresses [e.g., Stock , ; Schneider et al , ; Yohannes et al , ].…”
Section: Theoretical Frameworkmentioning
confidence: 99%